Multicultural-Based Education for Madrasah Ibtidaiyah Students During Covid-19 Pandemic - Farihin Farihin (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The purpose of the study was to investigate the strategy of internalizing multicultural-based character education for Islamic elementary school students (Madrasah Ibtidaiyah/MI) in the city of Salatiga during the pandemic. The research method used is qualitative with data collection techniques of observation, interviews, and documentation. The focus of the research is on the strategy of internalizing the values ​​of character education based on multiculturalism starting from the conception and stages in the internalization process consisting of exemplary strategies, habituation strategies, and MIS discipline strategies in Salatiga City. The findings reveal that the internalization strategy carried out by schools is through an integration strategy and the Implementation Strategy of Multicultural-based Moral Education at Home. The conclusion is that the strategy of internalizing multicultural-based character education during the pandemic focuses on the role of parents, the ability of teachers to design learning strategies, and digital technology-based learning models.